PENGARUH BUDAYA ORGANISASI (Panca Jiwa) TERHADAP KINERJA STAF UNIVERSITAS DARUSSALAM (Unida) GONTOR - Ilham Sainuddin; Fajar Surya Ari Anggara (University of Darussalam Gontor, 2021)
The problem in Indonesia nowadays is the weak quality of human resources. For this reason, discussions about performance are still very important. One of the things that guarantees the running of performance in accordance with the owner's expectations is organizational culture. Organizational culture is a set of values that characterize and guide the organization in carrying out the goals and solve organizational problems. The main value of organizational culture in this research is Five Spirits at University of Darussalam Gontor. The method in this research is a quantitative method with a sample of 58 staff from the University of Darussalam (UNIDA) Gontor. While the data analysis technique uses in this research is product moment correlation analysis, significance correlation coefficient test and coefficient determination. Based on the results of this research, shows that the relationship between variables is (r: 0.825) at very strong intervals, Then it shows the influence of the value of organizational culture (Five Spirits) on staff performance, with the level of influence (68.06%).